Combining GPS and VLBI for inter-continental frequency transfer. (11th March 2015) - Hobiger, T; Rieck, C; Haas, R; Koyama, Y
Abstract: For decades the global positioning system (GPS) has been the only space geodetic technique routinely used for inter-continental frequency transfer applications. In the past very long baseline interferometry (VLBI) has also been considered for this purpose and the method's capabilities were studied several times. However, compared to GPS current VLBI technology only provides few observations per hour, thus limiting its potential to improve frequency comparisons. We therefore investigate the effect of combining GPS and VLBI on the observation level in order to draw the maximum benefit from the strength of each individual technique. As a test-bed for our study we use the CONT11 campaign observed in 2011. First we review the frequency transfer performance that can be achieved with independent technique-specific analyses, both with individual software packages and with the multi-technique software c5++. With this analysis approach both techniques, GPS and VLBI, show similar frequency link instabilities at the level of 10 −14 to 10 −15 (MDEV) on inter-continental baselines for averaging times of one day. Then we use the c5++ software for a combined analysis of GPS and VLBI data on the observation level. We demonstrate that our combination approach leads to small but consistent improvements for frequency transfer of up to 10%, in particular for averaging periods longer than 3000 s.